An Automatic Approach for the Extraction of Road Junctions from High-Resolution Aerial Images - Pudaruth, Sameerchand (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
The problem of locating road junctions has received much less attention than the extraction of roads networks from high resolution aerial images. The problem of road detection has been in the minds of researchers for the last 30 years where junction detection is a relatively newer problem and some interesting work in this direction has been done in the last decade. The exact localization of junctions has paramount importance in the field autonomous driving vehicles. Thus, in this paper, we present a naive but a very effective road junction detector. The detector has been tested on a number of rural images and its accuracy is very high.